Pengembangan Sistem Informasi Manajemen Sumber Daya Manusia - Yuni Marlina Saragih; Winda Irma Wati Br Siagian; Fandi Halim; Zulpa Salsabila (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
A human resource management is an integrated system important to a company, resulting in a need for better employee attendance and the need for more informed decision-making regarding new employee recruitment management, employee appraisal, position placement, employee training, employee service, and employee dismissal. Because of these, an integrated system is needed in handling the attendance process until the employee termination. So as to meet the needs of the company in the management of data attendance of employees better by minimizing the occurrence of fault, reduce paper use and worktime of HR department in attendance recording and help HR managers on making more appropriate decisions related to existing processes in company such as helping on determining appropriate employees occupy positions based on position qualification with the employee ability. This Information System Development using System Development Lifecycle methodology (SDLC) begin with designing Fishbone Diagram, Data Flow Diagram (DFD), PIECES Diagram, system interface design, Microsoft Visual Studio 2012 as input, Microsoft SQL Server 2012 as data storage and SAP Crystal Reports as output in reports. The authors hope, the results of this information system development can help companies to deal with existing problems in human resource management.